Effect of Institutional Ownership, Company Size, Activity Ratio, Profitability and Managerial Ownership on Company Value - Ningsih, Dewi Ayu; Nurlaela, Siti; Rachmawati Dewi, Riana (INOVASI: Jurnal Ekonomi, Keuangan, dan Manajemen, 2025)
The purpose of this study is to find out how institutional ownership, company size, activity ratio, profitability, and management ownership affect company value. Goods and consumption sector companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2021 are the subject of the study. Using the purposive sampling method, this study selects companies listed on the Indonesia Stock Exchange (IDX) in the field of goods and consumption. These companies also issue complete financial statements and record their profits. The data was analyzed using multiple linear regression techniques. The results show that while institutional ownership, company size, activity ratio, and managerial ownership do not have a significant influence on company value, profitability has a significant influence